Europe in question referendums on European integration - Hobolt, Sara Binzer (Oxford : Oxford University Press, 2009)
This title explains how voters decide in referendums on European integration. It presents a comprehensive theoretical framework for understanding voting behaviour in referendums and a thorough comparative analysis of EU referendums from 1972 to 2008.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; European federation -- Public opinion; Public opinion -- European Union countries; Political campaigns -- European Union countries -- Evaluation; Referendum -- European Union countries; Europe -- Economic integration; European Union countries -- Politics and government